A CFD model for simulating wave run-ups and wave loads in case of different wind turbine foundations influenced by nonlinear waves. (1st January 2017) - Lin, Yu-Hsien; Chen, Jing-Fu; Lu, Po-Ying
Abstract: A hydrodynamic simulation of wave run-up heights and wave loads on three types of wind turbine foundations, i.e. monopile, gravity-based and tripod support structures, was conducted using a RANS solver and employing k-ε turbulent closure. Due to the contribution of the present CFD model, a semi-empirical formula is calibrated based on velocity stagnation head theory for crest kinematics. Eventually, the results indicate that the difference among the maximum normalized run-up heights of these support structures is smaller for lower wave steepness than those for higher wave steepness. In contrast, it is shown that the difference among the wave loads of these foundations is larger for lower wave steepness than those for higher wave steepness. A calibrated run-up parameter is also obtained by means of numerical simulation and found that the value of calibrated run-up parameter becomes smaller accompanied with larger values of wave steepness and the maximum normalized run-up height. It is relevant that the tendency of run-up heights is positively correlated with higher nonlinearity, whereas an opposite trend is observed in the relationship between larger calibrated run-up parameter and lower nonlinearity. Highlights: This study essentially discusses the 1 run-up heights accompanied with wave loads by comparing wave. Steepness parameter ka and scattering parameter kA for three different types of wind turbine foundations.